Response of Foliar Application of Growth Hormone and Nutrients on Plant Growth and Seed Yield in Carribbean Stylo Stylosanthes hamata - R.K. BHATT; R.K. TRIPATHI; H.S. TIWARI (Seed Research, 2026)
The shoot growth in terms of plant height increased by foliar application of growth hormone and nutrients in carribbean stylo Stylosanthes hamata. It was maximum by the application of NAA (100 ppm), whereas it decreased by the foliar application of cycocel (0.5 kg/ha). Rate of photosynthesis and stomatal conductance increased significantly by foliar spray of chemicals. Rate of photosynthesis significantly improved in the plants treated with GA3 (100 ppm) and NAA (100 ppm), followed by KNO3 (4 kg/ha), whereas the responses of boron (100 ppm) and cycocel (0.5 kg/ha) were at par. Maximum transpiration rate was recorded in the plants sprayed with NAA (100 ppm) and KNO3 (4 kg/ha). The flower production increased in plants with foliar spray of GA3 (100 ppm), followed by KNO3 (4 kg/ha), whereas NAA (100 ppm) and boron (100 ppm) application were at par. Maximum seed yield (232.85 kg/ha) in the plants treated with GA3 (100 ppm) and 221.54 kg/ha was recorded in plants treated with KNO3 (4 kg/ha) over the control (173.46 kg/ha). The seed yield increased by 3.5-34 per cent. The increase in seed yield might be due to increase in the number of flowers/plant as indicated by positive and significant correlation between these two parameters (r=0.9663). Maximum seed test weight (3.30 g) was recorded by the application of KNO, (4kg/ha), followed by 3.24 g GA3 (100 ppm) over the control.